The effect of maternal alcohol consumption on fetal growth and preterm birth. - O'Leary, C; Nassar, N; Kurinczuk, J; Bower, C (2009)
OBJECTIVE: To investigate the relationship between prenatal alcohol exposure and fetal growth and preterm birth and to estimate the effect of dose and timing of alcohol exposure in pregnancy. DESIGN: A population-based cohort study linked to birth information on the Western Australian Midwives Notification System. SETTING: Western Australia. POPULATION: A 10% random sample of births restricted to nonindigenous women who had delivered a singleton infant (n= 4719) in 1995-1997. METHODS: The impact of alcohol consumption in pregnancy on fetal growth (small-for-gestational-age [SGA] and large-for-gestational-age infants [LGA]) and preterm birth (<37 weeks of gestation) was assessed using multivariate logistic regression analysis and adjusting for confounding factors. MAIN OUTCOME MEASURES: Odds ratios and 95% CI, attributable risk, and population attributable risk were calculated. RESULTS: The percentage of SGA infants and preterm birth increased with higher levels of prenatal alcohol exposure; however, the association between alcohol intake and SGA infants was attenuated after adjustment for maternal smoking. Low levels of prenatal alcohol were not associated with preterm birth; however, binge drinking resulted in a nonsignificant increase in odds. Preterm birth was associated with moderate and higher levels of prenatal alcohol consumption for the group of women who ceased drinking before the second trimester. This group of women was significantly more likely to deliver a preterm infant than women who abstained from alcohol (adjusted OR 1.73 [95% CI 1.01-3.14]). CONCLUSIONS: Alcohol intake at higher levels, particularly heavy and binge drinking patterns, is associated with increased risk of preterm birth even when drinking is ceased before the second trimester. This finding, however, is based on small numbers and needs further investigation. Dose and timing of prenatal alcohol exposure appears to affect preterm delivery and should be considered in future research and health education.